BUMDes Business Plan Training in Tunah Village - Prihantono, Gigih; Sari, Dyah Wulan; Wasiaturrahma, Wasiaturrahma; Fithriyah, Fithriyah (Universitas Negeri Semarang, 2025)
Poverty alleviation and inclusive economic growth are agendas in sustainable development (Sustainable Development Goals/SDGs). One of the channels to alleviate poverty at the village level is to strengthen the institution of Village-Owned Enterprises (BUMDes). For this reason, a team of lecturers from the Department of Economics, Faculty of Economics and Business (FEB), Airlangga University (Unair) conducted community service in strengthening the institution of BUMDes Tunah Village to accelerate poverty reduction. Previously, it was known that the level of extreme poverty in Tunah Village reached 12%. This community service program was implemented in the form of training and assistance in preparing a business plan (Renbis) for the development of BUMDes Tunah Village. The final result of this activity is expected to be the preparation of a Renbis document as a guideline for the development of BUMDes Tunah Village to contribute to poverty reduction there.